2013
DOI: 10.1002/aic.14284
|View full text |Cite
|
Sign up to set email alerts
|

Numerical derivation of dispersion coefficients for flow through three‐dimensional randomly packed beds of monodisperse spheres

Abstract: The longitudinal (D L ) and transverse (D T ) dispersion coefficients for flow through randomly packed beds of discrete monosized spherical particles are studied. The three-dimensional (3-D) porous-medium model consists of thousands of spherical particles that are divided into cells using Voronoi diagrams. The relationship between the variation of the dual stream function and the vorticity between neighboring particles is derived using Laurent series. The whole flow pattern at low particle Reynolds number is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…A comprehensive investigation of the flow at the pore level may result in more sophisticated models with heterogeneous distributions of variables instead of the common assumption of homogeneous profiles (Andrigo et al 1999;Eigenberger 1992). To reveal the detailed flow within porous media, the pore level flow has been modelled theoretically and numerically (Geller and Hunt 1993;Hill et al 2001;Powers et al 1994;Payatakes 1982;Hellström et al 2010;Jourak et al 2013Jourak et al , 2014Fabricius et al 2016;Burström et al 2016). There is also some experimental work on the detailed scale.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive investigation of the flow at the pore level may result in more sophisticated models with heterogeneous distributions of variables instead of the common assumption of homogeneous profiles (Andrigo et al 1999;Eigenberger 1992). To reveal the detailed flow within porous media, the pore level flow has been modelled theoretically and numerically (Geller and Hunt 1993;Hill et al 2001;Powers et al 1994;Payatakes 1982;Hellström et al 2010;Jourak et al 2013Jourak et al , 2014Fabricius et al 2016;Burström et al 2016). There is also some experimental work on the detailed scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have modelled pore level flow, as such, theoretically or numerically, e.g. Geller and Hunt (1993), Hellström et al (2010b), Ljung et al (2012), Jourak et al (2014) and Fabricius et al (2016) and Pérez-Ràfols et al 2016). Also, experiments have been performed on simplified geometries like parallel tubes (Khayamyan et al 2014;Khayamyan and Lundström 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the average ratio between a straight line between two points in the porous media and the actual flow path. In the work by Jourak et al [19] it was concluded that the tortuosity factor for the gas phase within 3D randomly mono-sized spherical packing is in the range of 1.38-1.49. In the current study it is thus set to ς = 1.4 which also agrees well with what is suggested in other literature.…”
Section: Dpmentioning
confidence: 99%
“…However, when varying the turbulence intensity at the inlet it turns out that the exact value does not influence the overall result, see Figs. 16,17,18,and 19 where the turbulence intensity values used are based on simulation done with a relevant up-and downstream geometry. The difference between laminar and turbulent gas temperature for five points in the bed is plotted as a function of time to highlight the influence of turbulence and inlet intensity.…”
Section: Turbulencementioning
confidence: 99%
See 1 more Smart Citation